Community Participation In Sanitation Kampung Program, Surakarta - Anak Agung Alit Kirti Estuti Narendra Putri; Hermanu Joebagio; Dono Indarto (Journal of Health Promotion and Behavior, 2017)
Background: Indonesia ranks third in the world in the number of people with limited access to sanitation. Surakarta municipality government in collaboration with local drinking water supplier (PDAM) operate Indonesian Urban Water, Sanitation and Hygiene (IUWASH) to overcome sanitation problems in the form of Sanitation Kampung Program in Semanggi Village, Surakarta. This study aimed to review community participation in Sanitation Kampung Program, Semanggi Village.Subjects and Method: This was a qualitative study conducted at RW 23, Semanggi Village, Pasar Kliwon subdistrict, Surakarta, Central Java. Informants were selected purposively for this study comprising 12 community members as key informants, 2 community leaders, head of Sanitation Kampung Program, and 1 environmental health expert as supporting informants, The data were collected by in-depth interview, focus group discussion, and document review. Data credibility was checked by triangulation. The data were analyzed by content analysis.  Results: At the beginning of Sanitation Kampung Program planning there were some pros and cons from the community. Some of the community accepted the program but some others refused it due to negative perception that Sanitation Kampung Program would cause bad smell and pollute well water. In order to overcome community refusal toward Sanitation Kampung Program, IUWASH, Surakarta municipality government, and community leaders, carried out socialization, community approach, and study tour to other places. In the end, the community accepted Sanitation Kampung Program. Community members participated the program by providing support for water and sanitation facility development. Community members made use of the water and sanitation facility for daily activities. They also maintained the water and sanitation facility.Conclusion: By developing good and trustable collaboration, community participate in Sanitation Kampung Program from planning, developing, using,  and maintenance of the water and sanitation facility.Keywords: water, sanitation, community, participation, programCorrespondence: Anak Agung Alit Kirti Estuti Narendra Putri. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: kirtiestuti@gmail.com. Mobile: +6285643231616.Journal of Health Promotion and Behavior (2017), 2(3): 257-271https://doi.org/10.26911/thejhpb.2017.02.03.06